2021
DOI: 10.1111/1556-4029.14689
|View full text |Cite
|
Sign up to set email alerts
|

Fatal methemoglobinemia in three suicidal sodium nitrite poisonings

Abstract: Nitrites are chemicals widely used as preservatives for meat and as anti-microbial agents in other food. They are commonly available as sodium, potassium, or ammonium salts. Nitrites are also abundant in the environment and are naturally occurring in some fruits and vegetables. Nitrates (-NO −3 ) on the surface of food can become nitrites (-NO −2 ) by the action of the bacterial enzyme nitrate reductase. Nitrates and nitrites are water soluble, and the presence of both forms can be minimized by washing food. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 9 publications
2
13
0
3
Order By: Relevance
“…We read with great interest the recent publication of Dean DE et al [1] entitled "Fatal methemoglobinemia in three suicidal sodium nitrite poisonings." The authors reported 3 fatal cases of ingestion with sodium nitrite (NaNO 2 ) and made a very interesting review regarding the toxicological and pathophysiological mechanisms of toxicity.…”
Section: Editormentioning
confidence: 99%
“…We read with great interest the recent publication of Dean DE et al [1] entitled "Fatal methemoglobinemia in three suicidal sodium nitrite poisonings." The authors reported 3 fatal cases of ingestion with sodium nitrite (NaNO 2 ) and made a very interesting review regarding the toxicological and pathophysiological mechanisms of toxicity.…”
Section: Editormentioning
confidence: 99%
“…Between 2000 and recent years, there has been a distinct lack of cases with only 1 case in New Zealand in 2010 identified in the literature [23]. However, since 2019 the number of reported suicides using sodium nitrite has significantly increased compared to previous years [24][25][26][27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…Introduction: Nitrites are chemical compounds naturally present in the environment [1]. In addition to endogenous production, human exposure occurs due to multiple applications, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…in construction and food industry, and also in health [2]. Self-poisoning from ingested nitrites is an uncommon form of suicide [1]. However, several cases have already been reported [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation